2011
DOI: 10.1007/s00705-011-1017-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of fish iridoviruses isolated in Taiwan during 2001–2009

Abstract: To investigate the genetic relationships between field strains of iridoviruses gathered from various fish species in Taiwan, viruses that were collected from 2001 to 2009 were analyzed. Open reading frames encoding the viral major capsid protein (MCP) and adenosine triphosphatase (ATPase) were sequenced for phylogenetic analysis. Our results indicated that iridoviruses from Taiwan aquaculture fishes could be classified into two groups: prior to 2005, the viruses were closely related to members of the genus Ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 34 publications
(36 reference statements)
1
44
0
3
Order By: Relevance
“…This accession was obtained from barred knifejaw (rock bream) fingerlings from a disease outbreak in Taiwan during 2008 that had been recently imported as larvae from Korea. The barred knifejaw isolate exhibited the greatest similarity to the TRBIV megalocytivirus isolates, in contrast to all other isolates characterised during the same study (Huang et al 2011).…”
Section: Preliminary Pcr and Sequencing Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…This accession was obtained from barred knifejaw (rock bream) fingerlings from a disease outbreak in Taiwan during 2008 that had been recently imported as larvae from Korea. The barred knifejaw isolate exhibited the greatest similarity to the TRBIV megalocytivirus isolates, in contrast to all other isolates characterised during the same study (Huang et al 2011).…”
Section: Preliminary Pcr and Sequencing Resultsmentioning
confidence: 91%
“…However, all 3 forms of 'grouper iridovirus' (i.e. ISKNV megalocytivirus, RSIV megalocytivirus and ranavirus) have been documented from Taiwan (Huang et al 2011), and no details were provided by Chao et al (2004) to establish how megalocytiviral infection was confirmed, or which genotype was responsible, or whether a megalocytivirus was in volved at all. Consequently, the situation in 1980 is ambiguous and cannot be confirmed as the megalocytivirus index case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coldblooded vertebrate viruses, including the genera Lymphocystivirus, Ranavirus, and Megalocytivirus, are collectively called piscine iridoviruses because they are important causative agents of bony fish diseases (Kurita and Nakajima, 2012;Li et al, 2014). Furthermore, Ranavirus and Megalocytivirus are commonly associated with viral diseases of numerous kinds of groupers (Huang et al, 2011;Lü et al, 2005;Tsai et al, 2005). Thus, grouper iridovirus (GIV) mainly includes two different genera, namely, Ranavirus and Megalocytivirus, which belong to Iridoviridae.…”
Section: Introductionmentioning
confidence: 98%
“…Developing an ideal cell line for in vitro studies of cell-virus interactions, virus propagation, isolation and vaccine development is critical to disease control in aquaculture. Taiwanese iridovirus isolates consist of three major genotypes : grouper iridovirus (GIV) which belong to Ranavirus, red sea bream iridovirus (RSIV), and infectious spleen and kidney necrosis virus (ISKNV) that are classified to Megalocystivirus genuses [7]. Hence, development a continuous cell line from tropical fish species for identifying pathogenesis of viral diseases and for vaccine production is imperative.…”
Section: Introductionmentioning
confidence: 99%